INTERAKSI ANTARA PERCEIVED VALUE, TRANSACTION COST, DAN REPURCHASE INTENTION DALAM TRANSAKSI ON-LINE - Chairunnisa Chairunnisa; Anjar Priyono (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2018)
This research aims to analyse the relationships between perceived value, transaction cost and repurchase intention in on-line shopping environment. The respondents were selected purposively from customers who have completed at least a transaction during the last year. The instrument were developed using Likert Scale and analysed using structural equation modelling. In total, as many as 212 respondents completed the questionnaires. From the analysis it was revealed that consumer’s perceived value and repurchase intention have a positive influence in on-line shopping. In addition, it was shown that that information searching cost and moral hazard have negatif influence in perceived value. On the other hand information searching cost and specific asset investment showed negatif influence and positive influence on repurchase intention. Limitations and recommendations for future research are presented at the end of the paper.